Vertical arrays of SiNWs-ZnO nanostructures as high performance electron field emitters - Devarapalli, Rami Reddy; Shinde, Deodatta R.; Barka-Bouaifel, Fatiha; Yenchalwar, Sandeep G.; Boukherroub, Rabah; More, Mahendra A.; Shalke, Manjusha V. (Journal of Materials Chemistry, 2012)
Multicomponent hybrid materials of nanostructured building blocks are essential for the development of complex devices and advanced applications due to their role as either functional or interconnecting elements. This study introduces a simple and cost effective strategy for the synthesis of vertical arrays of silicon nanowires and ZnO nanostructures (nanorod and multipod structures). Formation of vertical nanostructured arrays is confirmed by SEM and HRTEM imaging as well as XRD and Raman measurements. We have investigated field emission properties of the as-synthesized vertical nanostructured arrays. Our results show that these SiNWs-ZnO nanostructures are highly efficient and stable field emitters.

High efficiency electron field emission from protruded graphene oxide nanosheets supported on sharp silicon nanowires - Devarapalli, Rami Reddy; Kashid, Ranjit V.; Deshmukh, Ashvini B.; Sharma, Ponchami; Das, Manash R.; More, Mahendra A.; Shelke, Manjusha V. (Journal of Materials Chemistry C, 2013)
Graphene oxide (GO) potentially has applications in vacuum microelectronic devices for realization of field emission displays. Graphene and its derivatives are expected to be efficient field emitters due to their unique electrical properties. However, the flat sheet structure of graphene or GO allows electron field emission only from the edges of graphene and GO nanosheets. In order to extract maximum field emission current density at lower applied voltage from the GO nanosheets, we supported and stretched them on sharp tips of silicon nanowires (SiNWs). Highly efficient and stable field emission with low turn-on field was observed for these SiNW-GO heterostructures. The sharp protrusions created by stretching of the GO nanosheets on SiNWs locally enhance the electric field and thus enhance the field emission characteristics. The dominant use of silicon in electronic devices makes this approach robust for the development of field emission devices using graphene based field emitters.

One-pot synthesis of gold nanoparticle/molybdenum cluster/graphene oxide nanocomposite and its photocatalytic activity - Barras, Alexandre; Das, Manash R.; Devarapalli, Rami Reddy; Shelke, Manjusha V.; Cordier, Stephane; Szunerits, Sabine; Boukherroub, Rabah (Applied Catalysis B-Environmental, 2013)
The paper reports on a facile one-pot synthesis of a tri-component gold nanoparticle/molybdenum cluster/graphene oxide (AuNPs@Mo-GO) nanohybrid composite. The synthetic methodology consists on direct UV irradiation of an aqueous solution containing graphene oxide (GO), Na-2[Mo6Br8(N-3)(6)], HAuCl4 center dot 3H(2)O and isopropanol at room temperature in air using a UV fiber lamp. The composite material exhibits very high photocatalytic activity for the degradation of rhodamine B under visible light irradation. The resulting nanohybrid material was characterized using Raman spectroscopy, UV-vis spectrometry, transmission electron microscopy (TEM) and X-ray photoelectron spectroscopy (XPS). (c) 2012 Elsevier B.V. All rights reserved.
Keywords: gold nanoparticles; graphene oxide; Nanohybrid; Photodegradation; Rhodamine B; visible light; [Mo6Br8(N-3)(6)](2-)cluster

C@SiNW/TiO2 core-shell nanoarrays with sandwiched carbon passivation layer as high efficiency photoelectrode for water splitting - Devarapalli, Rami Reddy; Debgupta, Joyashish; Pillai, Vijayamohanan K.; Shelke, Manjusha V. (Scientific Reports, 2014)
One-dimensional heterostructure nanoarrays are efficiently promising as high performance electrodes for photo electrochemical (PEC) water splitting applications, wherein it is highly desirable for the electrode to have a broad light absorption, efficient charge separation and redox properties as well as defect free surface with high area suitable for fast interfacial charge transfer. We present highly active and unique photoelectrode for solar H-2 production, consisting of silicon nanowires (SiNWs)/TiO2 core-shell structures. SiNWs are passivated to reduce defect sites and protected against oxidation in air or water by forming very thin carbon layer sandwiched between SiNW and TiO2 surfaces. This carbon layer decreases recombination rates and also enhances the interfacial charge transfer between the silicon and TiO2. A systematic investigation of the role of SiNW length and TiO2 thickness on photocurrent reveals enhanced photocurrent density up to 5.97 mA/cm(2) at 1.0 V vs. NHE by using C@SiNW/TiO2 nanoarrays with photo electrochemical efficiency of 1.17%.

Electrochemical preparation of vertically aligned, hollow CdSe nanotubes and their p-n junction hybrids with electrodeposited Cu2O - Debgupta, Joyashish; Devarapalli, Rami Reddy; Rahman, Shakeelur; Shelke, Manjusha V.; Pillai, Vijayamohanan K. (Nanoscale, 2014)
Vertically aligned, hollow nanotubes of CdSe are grown on fluorine doped tin oxide (FTO) coated glass substrates by ZnO nanowire template-assisted electrodeposition technique, followed by selective removal of the ZnO core using NH4OH. A detailed mechanism of nucleation and anisotropic growth kinetics of nanotubes have been studied by a combination of characterization tools such as chronoamperometry, SEM and TEM. Interestingly, ``as grown'' CdSe nanotubes (CdSe NTs) on FTO coated glass plates behave as n-type semiconductors exhibiting an excellent photo-response (with a generated photocurrent density value of similar to 470 mu A cm(-2)) white in contact with p-type Cu2O (p-type semiconductor, grown separately on FTO plates) because of the formation of a n-p heterojunction (type II). The observed photoresponse is 3 times higher than that of a similar device prepared with electrodeposited CdSe films (not nanotubes) and Cu2P on FTO. This has been attributed to the hollow 1-D nature of CdSe NTs, which provides enhanced inner and outer surface areas for better absorption of light and also assists faster transport of photogenerated charge carriers.

Functional silicon nanostructures derived from drying-mediated self-assembly of gold nanoparticles - Deshmukh, Ashvini B.; Devarapalli, Rami Reddy; Shelke, Manjusha V. (Journal of Nanoparticle Research, 2014)
Self-assembly of nanoparticles is an efficient technique where nanobuilding blocks spontaneously organize into ordered structures by thermodynamic and other constraints. We demonstrate that multifunctional Silicon (Si) nanostructures with unique morphologies like sheets, plates and flakes can be etched chemically by taking an advantage of natural self-assembly of gold nanoparticles (AuNPs) characterized with drying kinetics under external stimuli. We further demonstrated antireflection properties of the as-synthesized Si nanostructures.
Keywords: Antireflective material; gold nanoparticles; Metal-assisted chemical etching; Self-assembly; Si Nanostructures

Nanodiamond particles/reduced graphene oxide composites as efficient supercapacitor electrodes - Wang, Qi; Plylahan, Nareerat; Shelke, Manjusha V.; Devarapalli, Rami Reddy; Li, Musen; Subramanian, Palaniappan; Djenizian, Thierry; Boukherroub, Rabah; Szunerits, Sabine (Carbon, 2014)
The paper reports on the preparation of reduced graphene oxide (rGO) modified with nanodiamond particles composites by a simple solution phase and their use as efficient electrode in electrochemical supercapacitors. The technique relies on heating aqueous solutions of graphene oxide (GO) and nanodiamond particles (NDs) at different ratios at 100 degrees C for 48 h. The morphological properties, chemical composition and electrochemical behavior of the resulting rGO/NDs nanocomposites were investigated using UV/vis spectrometry, Fourier transform infrared (FTIR) spectroscopy, Raman spectroscopy, transmission electron microscopy (TEM) and electrochemical means. The electrochemical performance, including the capacitive behavior of the rGO/NDs composites were investigated by cyclic voltammetry and galvanostatic charge/discharge curves at 1 and 2 A g(-1) in 1 M H2SO4. The rGO/ND matrix with 10/1 ratio displayed the best performance with a specific capacitance of 186 +/- 10 F g (-1) and excellent cycling stability. (C) 2013 Elsevier Ltd. All rights reserved.

Plasmon-enhanced photocurrent generation from click-chemically modified graphene - Yenchalwar, Sandeep G.; Devarapalli, Rami Reddy; Deshmukh, Ashvini B.; Shelke, Manjusha V. (Chemistry-A European Journal, 2014)
The visible-light response of Au nanoparticles (AuNPs) assembled on rGO through different molecular bridges was investigated by transient photocurrent generation. We prepared rGO with two self-assembled monolayers (SAMs), one linear and the other with aromatic triazoles through a click cycloaddition reaction. A fivefold photocurrent enhancement was observed for triazole linkers over the aminopropyltrimethoxysilane (APTMS) linker. Cyclic voltammetry (CV) and impedance measurements also suggest fast electron transfer on account of the low resistance offered by the click-modified rGO surface whereby introduction of triazoles offers the efficient bridge between the donor AuNPs and acceptor rGO.
Keywords: Gold; graphene; Nanoparticles; photophysics; surface plasmon resonance

Quantum dot-decorated silicon nanowires as efficient photoelectrodes for photoelectrochemical hydrogen generation - Devarapalli, Rami Reddy; Kamaja, Chaitanya Krishna; Shelke, Manjusha V. (Journal of Materials Chemistry A, 2014)
Quantum dot-decorated wide band gap semiconductors, such as TiO2, ZnO, SnO2, etc., which have electron mobilities of less than 200 cm(2) V-1 S-1 have been well studied as the photoelectrodes for photovoltaics and photoelectrochemical water splitting. Herein, we report CdSe quantum dot decorated-silicon nanowires (SiNWs) as photoelectrodes for photoelectrochemical water splitting. SiNWs have a comparatively higher electron mobility than metal oxides. A photocurrent density of around 6.1 mA cm(-2) was obtained for the CdSe/SiNWs photoelectrode, which is nearly five times higher than that for SiNWs alone and which also shows a good transient photocurrent response. The band energy level alignment was also studied between Si and CdSe by observing the corresponding flat band potentials from a Mott-Schottky analysis.

Facile green synthesis of BCN nanosheets as high-performance electrode material for electrochemical energy storage - Karbhal, Indrapal; Devarapalli, Rami Reddy; Debgupta, Joyashish; Pillai, Vijayamohanan K.; Ajayan, Pulickel M.; Shelke, Manjusha V. (Chemistry-A European Journal, 2016)
Two-dimensional hexagonal boron carbon nitride (BCN) nanosheets (NSs) were synthesized by new approach in which a mixture of glucose and an adduct of boric acid (H3BO3) and urea (NH2CONH2) is heated at 900 degrees C. The method is green, scalable and gives a high yield of BCN NSs with average size of about 1 mm and thickness of about 13 nm. Structural characterization of the as-synthesized material was carried out by several techniques, and its energy-storage properties were evaluated electrochemically. The material showed excellent capacitive behaviour with a specific capacitance as high as 244 F g(-1) at a current density of 1 A g(-1). The material retains up to 96% of its initial capacity after 3000 cycles at a current density of 5 A g(-1).
Keywords: boron; Doping; Electrochemistry; Nanoparticles; nitrides

Glucose-derived porous carbon-coated silicon nanowires as efficient electrodes for aqueous micro-supercapacitors - Devarapalli, Rami Reddy; Szunerits, Sabine; Coffinier, Yannick; Shelke, Manjusha V.; Boukherroub, Rabah (ACS Applied Materials & Interfaces, 2016)
In this study, we report on carbon coating of vertically aligned silicon nanowire (SiNWs) arrays via a simple hydrothermal process using glucose as carbon precursor. Using this process, a thin carbon layer is uniformly deposited on the SiNWs. Under optimized conditions, the coated SiNWs electrode showed better electrochemical energy storage capacity as well as exceptional stability in aqueous system as compared to uncoated SiNWs. The as-measured capacitance reached 25.64 mF/cm(2) with a good stability up to 25000 charging/discharging cycles in 1 M Na2SO4 aqueous solution.
Keywords: carbon coating; glucose precursor; hydrothermal; microsupercapacitors; silicon nanowires

Synthesis of novel Cu2S nanohusks as high performance counter electrode for CdS/CdSe sensitized solar cell - Kamaja, Chaitanya Krishna; Devarapalli, Rami Reddy; Dave, Yasha; Debgupta, Joyashish; Shelke, Manjusha V. (Journal of Power Sources, 2016)
An important component of quantum dot sensitized solar cells (QDSSC) is the counter electrode which mediates the regeneration of oxidized quantum dots by reducing the polysulphide electrolyte. However, design and synthesis of an efficient counter electrode material is a challenging task. Herein, we report the synthesis of a unique Cu2S nanohusks directly on FTO coated glass substrates by electrodeposition and used as a counter electrode in QDSSC. When these electrodes are used for the reduction of polysulfide electrolyte in QDSSC, they exhibit higher catalytic activity and photovoltaic performance as compared to the Platinum counter electrode. The power conversion efficiency of about 4.68% has been achieved by optimizing the deposition time of Cu2S. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: counter electrode; Cu2S electrodeposition; Cu2S nanohusks; Quantum dot-sensitized solar cell

Co-catalytic metal oxide nanoparticles decorated silicon/hematite core shell nanowire arrays as efficient photo electrodes for water splitting - Devarapalli, Rami Reddy; Kamaja, Chaitanya Krishna; Shelke, Manjusha V. (ChemistrySelect, 2017)
By looking global energy demands, development of highly efficient stable semiconductor photoelectrodes for photoelectrochemical (PEC) water splitting is highly desirable. Herein, we have fabricated co-catalytic nanoparticles decorated Silicon nanowire (SiNWs)/Hematite(Fe2O3) core sell structures as photo anodes and studied the PEC water oxidation properties. As, Fe2O3 possess weak oxidation kinetics, decoration of NiO and Co3O4 nanoparticles on SiNW/Fe2O3 by hydrothermal method, which acts as co-catalysts to improves the water oxidation reactions. It was found that decoration of Co3O4 nanoparticles enhances the photocurrent up to 2.6 times, whereas for NiO nanoparticles improvement is of 1.5 times when compared to the undecorated electrodes. Along with enhancement of photocurrents, it also shows shift of onset potentials. The effect of the co-catalytic nanoparticles on the enhancement of photocurrent and charge transfer resistance at the interface of electrode-electrolyte have been studied by electrochemical impedance spectroscopy. Further, flat band potentials of the photo electrodes have been measured by using Mott-schottky analysis.
Keywords: Co-catalysts; photo anodes; Photoelectrochemical cell; silicon nanowires; water splitting

Facile synthesis of 3D anode assembly with Si nanoparticles sealed in highly pure few layer graphene deposited on porous current collector for long life Li‐Ion battery - Shelke, Manjusha V.; Gullapalli, Hemtej; Kalaga, Kaushik; Rodrigues, Marco; Devarapalli, Rami Reddy; Vajtai, Robert; Ajayan, Pulickel M. (Advanced Materials Interfaces, 2017)
With its exceptional theoretical charge capacity, silicon holds great promise as an anode material for realization of high energy density Li-ion batteries. However, extensive volume expansion and poor cycle stability of silicon compromise its actual use. In an effort to tame volume expansion and structural disintegration during cycling, an innovative 3D electrode assembly is fabricated involving continuous layer of graphene coated on porous current collector and Si nanoparticles sealed in as an active material. Graphene deposition and pore formation in metal current collector is achieved in a unique single step synthesis. All the active components like current collector, reacting material, and conducting material are manipulated in a way to produce synergistic architecture in a chemical vapor deposition process. Highly pure graphene deposited in this process enables efficient electron transfer from allover of the surface of silicon nanoparticles and prevents continuous solid electrolyte interphase layer formation. This binder free anode assembly shows extremely stable lithium storage performance for over 1000 cycles with 88% of initial capacity retention and 100% Coulombic efficiency.

One-step synthesis of a MoS2-CuS composite with high electrochemical activity as an effective counter electrode for CdS/CdSe sensitized solar cells - Kamaja, Chaitanya Krishna; Devarapalli, Rami Reddy; Shelke, Manjusha V. (Chemelectrochem, 2017)
Inorganic nanostructured composite materials involving metal sulfides are increasingly important in electrochemical applications like solar cells. In this research, we have developed a one-step in situ solvothermal method to synthesize a MoS2-CuS composite. MoS2 sheets increase electron-transfer ability, assisting the improvement in catalytic activity of the MoS2-CuS counter electrode. The charge-transfer resistance derived from impedance spectroscopy for the MoS2-CuS composite counter electrode at the electrode/electrolyte interface is very low, as compared to MoS2, mostly owing to the increased number of active catalytic sites for the reduction of polysulfide electrolyte. The Tafel polarization plot shows excellent electrocatalytic activity of the MoS2-CuS composite towards polysulfide electrolyte. Finally, the CdS/CdSe sensitized solar cell achieves a power conversion efficiency of about 5% upon optimization of the MoS2-CuS composition.

Carbon fabric based solar steam generation for waste water treatment - Higgins, M. W.; Rahmaan, Shakeel A. R.; Devarapalli, Rami Reddy; Shelke, Manjusha V.; Jha, Neetu (Solar Energy, 2018)
Decontamination of waste water is one of the most practical techniques to tackle the worldwide clean water shortage. In recent times, solar steam based decontamination of contaminated water has been attested as a potential sustainable strategy to get clean water using renewable resources. Herein, we report the utilization of Carbon fabric and Titanium Nanorods on Carbon Fabric for solar steam based water purification techniques. The performance of Carbon Fabric was tested under different conditions and the results proved that Carbon Fabric has excellent light to heat conversion capabilities in both real and ideal conditions. Owing to the excellent performance of Carbon Fabric, it was used for purification of different types of contaminated water. About 99.9% of salt and 87% of organic contaminants were removed from saline water and organic waste water respectively, using a simple low cost carbon fabric based homemade prototype. We also present the application of Titanium Nanorods on carbon fabric for the efficient removal of dye molecules like Rhodamine B from contaminated water using solar driven interfacial steam generation mechanism.
Keywords: Desalination; Dye degradation; Solar steam; Waste water treatment

Ni(OH)(2)-Fe2O3/CNOs ternary nanocomposite designed as an anode with complementary properties for high-performance li-ion battery - Dwivedi, Pravin Kumari; Muniraj, Vedi Kuyil Azhagan; Devarapalli, Rami Reddy; Shelke, Manjusha V. (Chemistryselect, 2018)
Synthesis of the new ternary hybrid composite with excellent electrochemical performances for Li-ion battery is demonstrated. The ternary hybrid composite of Ni(OH)(2)-Fe2O3/Carbon Nano Onions (NFOC) is synthesized by using two-step solution phase method delivers a high reversible discharge capacity of 928 mAhg(-1) at 50 mAg(-1) and 673 mAhg(-1) at a higher current density of 1000 mAg(-1) with excellent rate performance. Additionally, it shows to have stable cycle life up to 1000 cycles with 96% capacity retention and more than 99% of coulombic efficiency. The synergetic effect between Ni(OH)(2), Fe2O3 and carbon nano onions (CNOs) as well as the unique feature of heterostructures are responsible for the improved electrochemical performance of the battery. The reversible reaction of Fe2O3 and Ni(OH)(2) with Li, maintains its long cycle life with higher reversible discharge capacity and CNOs improve the efficient electronic transfer, accommodate substantial volume expansion and maintain the structural integrity of the material during lithiation-delithiation process.
Keywords: Heterostructures; Long cycle stability; Superior rate capability; Ternary Composite; Transition metal oxides